Oxygen vacancies and their role on the magnetic character of polycrystalline CeO2. Issue 3 (1st February 2023) - Paulin, M.A.; Alejandro, G.; Lamas, D.G.; Quintero, M.; Fuentes, R.O.; Gayone, J.E.; Butera, A.; Leyva, A.G.; Sacanell, J.
Abstract: The structural, electronic and magnetic properties of high purity nanostructured CeO2 powders were investigated under various reducing atmospheres. By performing in situ experiments, it was demonstrated that the appearance of oxygen vacancies promotes a paramagnetic behaviour in an initially diamagnetic oxide. This conclusion is inferred through a careful and detailed correlation between the magnetic measurements and the analysis of the electronic properties, obtained by X-ray absorption experiments under different atmospheres. After exposing the CeO2 powders to a reducing atmosphere, a residual state is obtained and the samples continue to exhibit a paramagnetic behaviour characterized by lower susceptibility values than those obtained during the in situ experiments. The results of ex situ Electronic Paramagnetic Resonance (EPR) measurements at room temperature further support the finding of paramagnetic behaviour in all the samples. EPR was used to characterize the electronic defects ascribed to intrinsic oxygen vacancies already present in the "as prepared" samples and extrinsic oxygen vacancies originated during the reducing treatments. The quasi-linear dependence observed between the intensity of the EPR signal characteristic of annealed samples and the duration of the corresponding reducing treatment suggests that there is a direct correlation between the paramagnetic residual state and the creation of extrinsic oxygen vacancies that occurs at high temperature under reducing atmosphere.